Gender differences in responses to an altruistic message regarding rubella vaccination - Okuno, Hideo; Satoh, Hiroshi; Arai, Satoru; Suzuki, Motoi; Kikkawa, Toshiko (Frontiers in Public Health, 2024)
Background The supplementary immunization activity (SIA) for the rubella vaccination of adult men born between 1962 and 1978 began in 2019 in Japan because of a vaccine gap in the cohort, as vaccination was not mandatory for those born in that period. However, SIA coverage remains low, despite an active campaign and financial support. Methods We conducted a randomized controlled study based on a 2 (scenario: self-vaccination, child vaccination) × 2 (message: self-interest, group-interest) factorial design, using a Japanese online panel. Participants with children were assigned to the child vaccination scenario in Intervention 1, whereas others were assigned to the self-vaccination scenario. After Intervention 1, all participants were given the same information about rubella. In Intervention 2, participants assigned to self-interest messages received a message emphasizing the risk of rubella, and those assigned to group-interest messages received a message emphasizing herd immunity. After Intervention 2, we evaluated the effects using a questionnaire. Results Among the 2,206 participants, information regarding rubella was evaluated as more reliable in the group—than in the self-interest message condition, especially among women. Women evaluated the necessity of rubella vaccination for adult men and women to be higher in the child-vaccination scenario and group-interest messages. However, no differences were found among men. By contrast, men exposed to the self-interest message positively evaluated the reliability of the rubella explanation. Conclusion The findings indicate that emphasizing self-interest messages is more effective for men in promoting herd immunity against rubella.